Characterisation and quantification of cavities in 9Cr martensitic steel for power plants. (March 2015) - Yadav, S. D.; Sonderegger, B.; Sartory, B.; Sommitsch, C.; Poletti, C.
<x content-type="archive" xml:space="preserve">Abstract</x> This work focuses on the characterisation of cavities evolution in a P91 steel pipe in three conditions: as received, and after creep at 650°C and 60 MPa for 7000 and 9000 h. A field emission gun scanning electron microscope (FEG-SEM) equipped with focused ion beam (FIB) gun, a conventional scanning electron microscope (SEM) and a light optical microscope (LOM) have been employed for the investigation. This study reveals two types of cavities: the pre-existing cavities, which are rare in this type of heat resistant steels, with a mean diameter of 2·56 μm and the cavities produced during creep with diameters smaller than 0·6 μm. Lath boundaries and precipitates are found to be preferential sites for cavity nucleation. Furthermore, the number density and volume fraction of these small cavities are calculated from 2D measurements and compared to 3D results obtained by FIB serial sectioning.